THE RELATION BETWEEN RESOURCES AND WASTE BANK PROGRAM WITH THE SUCCES OF WASTE BANK IN YOGYAKARTA - agustin arizkyani; Surahma Asti Mulasari (Universitas Ahmad Dahlan, 2021)
Background : The problem of waste in Indonesia is not only a lack of technical, social, economic and cultural, but covers all aspects of human life. Community-based waste management of which is waste bank program. Implementation of waste bank program will not run smoothly without any quality resources and waste banks a good program. The aim of this study was to determine the relationship between resources and bank program to the success of the bank trash bins in the city of Yogyakarta.Methods : The study is an observational analytic research with cross sectional approach to study design (cross-sectional) is a research to study the dynamics of the relationship between resources and programs with the success of the bank's bank rubbish bins. Data analysis using chi square test.Results : Based on statistical test revealed that there was no relationship between the amount of garbage bank manager with success in the city of Yogyakarta. This is evidenced from the value (P Value 0.092> 0.05). There is no relationship between education and success garbage bank in Yogyakarta. This is evidenced from the value (P Value 0.299> 0.05). There is no relationship between program success bank banks bins with garbage in the city of Yogyakarta. This is evidenced from the value (P Value 0.665> 0.05). There is no relationship between the bank operational schedule of garbage with garbage bank's success in the city of Yogyakarta. This is evidenced from the value (P Value 0.222> 0.05).Conclusion : This study concluded that there was no correlation between the resources and programs with success bank bank rubbish bins in the city of Yogyakarta.